A Sociological-Conceptual Genealogy of Post-Secularization - Gil-Gimeno, Javier; Rodríguez-Lizarraga, Lucía Mª (’Ilu. Revista de Ciencias de las Religiones, 2025)
Recent analyses by José Casanova, Jürgen Habermas, Gordon Lynch, Hans Joas, Robert Bellah, David Martin or the latest Peter Berger -among others- have focused on the limitations associated with the general theory of secularization, which for decades became the paradigm from which to understand and interpret the relations between the secular and the religious. Through the theory of post-secularization, it has been possible to re-grade the sociological view of these relationships, emphasizing the vitality and plurality of forms that the religious currently acquires. Starting from this presupposition, the objective of our work is to carry out a sociological-conceptual genealogy of post-secularization centered on the analysis of some of the main theoretical contributions that have contributed to the development of this new approach to secularization. This genealogy will not be limited to the analysis of the work of authors who have articulated their proposals as a response to the inadequacies of the general theory of secularization, but we also want to study briefly some contributions of classics of sociological thought -specifically Durkheim and Weber- whose reflections already pointed to a post-secularization horizon. Thus, after the introduction, we will present a first section focused on the study of modern polytheism according to Weber and the sacred thing in Durkheim’s work. Subsequently, we will present three current theoretical analyses, namely those of Habermas, Casanova and Lynch, which will help us to outline the conceptual contours of post-secularization.